The development of the concept of episcopacy in the Church of England from the nineteenth to the mid-twentieth centuries - Weishaupt, S (2013)
The purpose of this thesis is to examine the Church of England’s understanding of ‘episcopal’ episcopacy and ordained ministry, including their ecclesiological implications and ecumenical consequences. Special attention is given to the refusal of interchangeability of ordained ministers with ‘non-episcopal’ churches (whilst allowing inter-communion), on the grounds that they lacked a ‘historic succession’ of bishops (cf. The Meissen Declaration and Agreement). This claim gives the adjective ‘episcopal’ a denominational, (quasi-)sacramental connotation (hence the inverted commas). Official Anglican statements today claim that the concept of episcopacy in a ‘historic succession’ is and always has been an integral part of ‘Anglican’ teaching as part of its ‘Catholic’, pre-Reformation heritage, whereas it appears that before the nineteenth century the Church of England had been defined largely in territorial and institutional terms. This faced challenges both from without and within, with an increasingly secular and multi-denominational context in Britain (with Non-conformists slowly gaining equal social and political rights) and in the face of the emergence of the Anglican Communion (and ecumenism in the twentieth century). This required the Church of England to forge a distinctive, trans-national, denominational identity for itself and for ‘Anglicanism’ (which can be described as the ‘Anglicanization of the Church of England’). In the first half of the nineteenth century, the English episcopate exercised a more active leadership role (the ‘episcopalization of the Church of England’), creating bishoprics in overseas dependencies and strengthening the influence of the Church of England there and also that of the episcopate (a colonial aspect of the ‘Anglicanization’). In the second half of the nineteenth century the bishops established interchangeability of ministers with formerly English, ‘Episcopal’ churches. This development occurred at the high point of Anglo-Catholic and ritualistic influence (which resulted in a ‘Catholicization of the Church of England’, opposed by Evangelicals and High-churchmen of the pre-Tractarian type). The nature of ‘Anglicanism’ was increasingly interpreted as ‘catholic’/‘Catholic’. In the twentieth century the notion of a ‘historic succession’ of bishops eventually appeared in official documents, whereas earlier statements had been insisting on the ‘historic episcopate’, but open to an understanding in the sense of ‘apostolic succession’ or a divinely instituted or sanctioned, or simply ancient form of government (episcopacy as esse, plene esse or bene esse of church). The eventual adoption of the notion of succession, however, the crucial characteristic of the esse model, meant a ‘theologization’ of Anglican ecclesiology in the late nineteenth and early twentieth centuries with a distinct ‘catholic’ character, which explains the refusal to agree on interchangeability of ministers with ‘Protestant’ churches, now on theological grounds.